THU0017 Combination of egfr and blys gene expression in lupus nephritis. (15th June 2017) - Mas, LA; Retamozo, S; Bonisconti, F; Palomino, EV; Pirola, JP; Saurit, V; Alvarellos, A; Alvarellos, T
Abstract : Background: Lupus nephritis (LN) is a severe complication of Systemic Lupus Erythematosus (SLE). Non-invasive biomarkers are needed for diagnosis of LN and to identify patients at risk of a renal flare (1). Thus the presence of biomarkers associated with inflammation, tissue damage or cell activation in the urine of patients with LN may be a useful tool in the evaluation of LN patients. The glomerular filtration rate (GFR) is considered the best overall index of renal function in health and disease. Because GFR is difficult to measure in clinical practice, most clinicians estimate the GFR (eGFR) from the serum creatinine concentration (2). B Lymphocyte Stimulator (BLyS) is a cytokine that fosters B cell activation, antibody production, B cell - T cell interaction and plasma cell survival. These events have been demonstrated to play a role in patients with LN (3). Objectives: We evaluated urinary levels of BLyS as biomarker for LN and their relationship with eGFR. Methods: Urine samples (n=86) were obtained from LN patients and classified in two groups: patients with eGFR >60 (GFRhigh, n=68, 62F/6M, age: 34.07±13.24) and patients with eGFR ≤60 (GFRlow, n=18, 14F/4M, age: 35.22±13.76). RNA from urine samples was isolated using TRIzol-Chloroform technique and then reverse-transcribed using random primers. Levels of BLyS expression were evaluated using Quantitative Real Time PCR (QPCR). All amplifications were carried out in duplicate and threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting the corresponding β2Microglobuline (β2M) control, or DCt=Ct, gene - Ct, B2M .To test for differential gene expression between groups, a two sample t-test was performed to compare the DCt in the two groups. Results: DCt is inversely proportional to BLyS's expression. We evaluated data from ΔCt analysis observing that mRNA levels of BLyS in eGFRlow (6.193±1.787) were higher than those from eGFRhigh (7.564±2.326), with a statistically significant difference between groups (p=0.0288). Conclusions: In the present cross-sectional study, increased levels of BLyS were observed in patients with eGFR ≤60. These gene expression results might be linked to B cell activation and proliferation in kidney and thus in urine samples. Combination of eGFR and BLyS appears to be a good biomarker. References: Rahman A. Can measuring urinary biomarkers improve the management of lupus nephritis? Arthritis Research & Therapy 2012, 14:127. Levey AS, Bosch JP, Lewis JB, Greene T, Rogers N, Roth D. A more accurate method to estimate glomerular filtration rate from serum creatinine: a new prediction equation. Modification of Diet in Renal Disease Study Group. Ann Intern Med. 1999 Mar 16; 130 (6):461–70. Phatak S, Chaurasia S, Mishra SK, Gupta R, Agrawal V, Aggarwal A, Misra R. Urinary B cell activating factor (BAFF) and a proliferation inducing ligand (APRIL): potential biomarkers of active lupus nephritis. Clin Exp Immunol. 2016. Epub ahead of print. Disclosure of Interest: None declared